PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DALAM MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN BANJARSARI 01 KABUPATEN MADIUN TAHUN PELAJARAN 2015/2016 - Harsanti, Arni Gemilang (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Low student learning outcomes to social studies is a problem that often arises in social studies learning. This is because the learning model still did not agree with the teaching objectives. Learning through learning model is expected to make a match the students' understanding and absorption of the material being taught can be achieved more quickly. Through this learning teachers deliver structured learning materials related to real life in the hope of the subject matter presented can be controlled by the student well and create a pleasant learning environment for students. This study aims to determine whether the implementation of cooperative learning model make a match in improving student learning outcomes in social studies teaching and learning activities in the classroom. This research is a classroom action research (PTK), which is carried out in three cycles of study with the matter "Maintaining Independence Struggle Indonesia". The subjects of this study were students of class V SDN Banjarsari 01 which consists of 24 students. Data collection was performed by the method of observation and tests. Analysis technique used is descriptive analysis techniques, the data obtained were analyzed by means checked for then classified into patterns, relationships, a theme or a particular category to the next is described using words to derive a conclusion. Based on test data studied is known that in the first cycle students who pass the study is still small, at only 33.3% of the total student with an average value of 62.50. In the second cycle increased to 62.5% with an average value of 69.37 and in Cycle III back has increased, reaching 87% with an average grade reaches 81.25. This indicates that learning by applying cooperative learning model Make a Match can improve learning achievement IPS fifth grade students of SDN 01 Banjarsari school year 2015/2016. Keywords : Learning Model Make a Match, Learning Outcomes.